China's United Front Work in the Xi Jinping era – institutional developments and activities. Issue 1 (2nd January 2019) - Suzuki, Takashi
ABSTRACT: [Background] To make China a superpower, Xi Jinping has provided the United Front Work (UFW) with large-scale resources to secure China's domestics stability and global outreach of its national power. [Purpose] This article investigates why and how the Chinese Communist Party (CCP) under Xi administration has been vigorously trying to co-opt politically non-communist forces at home and abroad by means of the UFW. The above analysis also sheds ligt on the characteristics of Xi's political thought, leadership style as well as his idea of political strategy for the "Great Rejuvenation of the Chinese Nation (zhonghua minzu weida fuxing)." [Main Argument] In foreign activities, China's influence through developing various UFW institutional settings has been strengthened. However, its construction of human network which contributes to CCP's political aims and its maintenance of information flaw bases have been mostly made up of personal effort in the long-term activity of the UFW. [Conclusions] It is true that the democratic regimes need to adopt a cautious approach toward China's foreign influence, but to identify activities of the UFW in their homeland is not so much difficult because they are usually patterned in most cases. Then, in the research on the UFW, Xi Jinping's political conservativeness has again become highlighted. The basic orientation of his political thinking is not the reform and innovation of the regime, but the revival of 'good tradition' and renovation of the CCP.